AKTIVITAS EKOENZIM KULIT NANAS (Ananas comosus (L). MERR) VARIETAS TANGKIT SEBAGAI ANTISEPTIK ALAMI TERHADAP Escherichia coli DAN Staphylococcus aureus - Pratama, Hefzi Prasetyo Azri; Syah, Putri Indriaty; Royhan, Ibnu; Maritsa, Hasna Ul; Yusuf, Ashif Irvan (Universitas Jambi, 2025)
Bacteria are one of the causes of disease in humans, there are various types of bacteria in the environment that can infect humans either directly or by vectors. Escherichia coli and Staphylococcus aureus bacteria are bacteria that are often found in everyday life. One effective effort to fight these bacteria is to wash hands with cleaning agents. One of the natural cleaners that can be used as hand soap is ecoenzyme from pineapple skin because it contains antibacterial substances such as vitamin C, Carotenoids and Flavonoids. In addition, pineapple skin also contains tannins, saponins, phenols, carbohydrates, terpenoids, alkaloids, phenols, anthraquinones, and amino acids. In addition to having a rich content of secondary metabolite compounds, pineapple skin is also not utilized so that pineapple skin waste is widely found. This makes pineapple skin waste very suitable to be processed into ecoenzymes and used as antibacterial cleaning agents. The purpose of this study was to determine the ability of pineapple ecoenzyme to inhibit the growth of Escherichia coli and Staphylococcus aureus bacteria and to determine the effectiveness value of pineapple ecoenzyme in inhibiting the growth of Escherichia coli and Staphylococcus aureus bacteria. The method used in this study was the test of ecoenzyme inhibition activity against Escherichia coli and Staphylococcus aureus bacteria using discs. There were 4 treatments, namely 25%, 50%, 75%, 100% ecoenzyme and 4 replications were made. Based on the results of the study, it is known that the effectiveness of pineapple peel waste ecoenzyme has a weak category with the highest concentration inhibiting Escherichia coli bacteria of 4.75 mm at a concentration of 100%, while Staphylococcus aureus bacteria had 2.75 mm at a concentration of 75%. The 70% alcohol control has an inhibitory power against both bacteria which is still higher than Escherichia coli and Staphylococcus aureus bacteria.